Reaktualisasi Proses Penyidikan oleh Kepolisian Berbasis Nilai-Nilai Pancasila dan Optimalisasi Pemanfaatan Teknologi - Ira Alia Maerani (Jurnal Hukum, 2015)
Abstract                Indonesian Criminal Justice System consists of the police, public prosecutor and the courts. The role of the police investigators is certainly vital as the frontline in building public confidence in the rule of law in Indonesia. The role of the investigator is quite important in realizing society’s  justice. The era of globalization requires a pattern fast-paced, instant, measurable, and transparent of life and it requires investigators to follow the times by optimizing the use of technology. The aim of this study is to give effect to the rule of law in Indonesia that provides fairness, expediency and certainty. However, it considers to have priority of Pancasila values in the process of inquiry and investigation. The values of supreme divinity, God (religious), humanity, unity, democracy and justice are values that establish a balance (harmony) in enforcing the law. Law and its implementation can create product which meets the demands for social justice. This paper will examine the role of the investigator according to positive law currently in force as well as the role of investigator in implementing the values of Pancasila, accompanied by optimizing the use of technology. Keywords: Re-actualizing, Investigation, Police, values of Pancasila, Technology   AbstrakSistem Peradilan Pidana Indonesia meliputi institusi kepolisian, kejaksaan, dan pengadilan. Peran penyidik dalam institusi kepolisian tentunya amat vital sebagai garda terdepan dalam membangun kepercayaan masyarakat terhadap penegakan hukum di Indonesia. Peran penyidik amat besar dalam terwujudnya keadilan di masyarakat. Era globalisasi yang menuntut pola kehidupan yang serba cepat, instan, terukur, dan transparan menuntut penyidik untuk mengikuti perkembangan zaman dengan mengoptimalkan pemanfaatan teknologi. Tujuannya adalah untuk memberikan arti bagi penegakan hukum di Indonesia yakni memberikan keadilan, kemanfaatan, dan kepastian. Namun yang harus diperhatikan adalah mengutamakan nilai-nilai Pancasila dalam melakukan proses penyelidikan dan penyidikan. Nilai-nilai ketuhanan yang maha esa (religius), kemanusiaan, persatuan, kerakyatan dan keadilan merupakan nilai-nilai yang membangun keseimbangan (harmoni) dalam menegakkan hukum. Sehingga produk hukum dan pelaksanaannya memenuhi rasa keadilan masyarakat. Tulisan ini akan mengkaji tentang peran penyidik menurut hukum positif yang saat ini berlaku serta peran penyidik dalam mengimplementasikan  nilai-nilai Pancasila dengan diiringi optimalisasi pemanfaatan teknologi.Kata Kunci: Reaktualisasi,Penyidikan,Kepolisian,Nilai-nilai Pancasila,Teknologi